MODEL IMPLEMENTATION OF MODERN METHODS FOR IMPROVING THE QUALITY OF ACADEMIC ADMINISTRATIVE SERVICES IN THE SCHOOL OF INDUSTRIAL ENGINEERING - UNMSM - Yenque De Dios, Julio (1999)
Every institution must ensure quality service to; for this reason, in this paper, I present some lines of action, identify common conflicts, determine the degree of job satisfaction and highlight the problems that can be solved implement modern methods to improve the quality of service in the FII-San Marcos.